REV-ERBα Regulates TH17 Cell Development and Autoimmunity - Mohammed Amir; Sweena Chaudhari; Ran Wang; Sean Campbell; Sarah A. Mosure; Laura B. Chopp; Qun Lu; Jinsai Shang; Oliver B. Pelletier; Yuanjun He; Christelle Doebelin; Michael D. Cameron; et al. (Cell Reports, 2018)
Summary: RORγt is well recognized as the lineage-defining transcription factor for T helper 17 (TH17) cell development. However, the cell-intrinsic mechanisms that negatively regulate TH17 cell development and autoimmunity remain poorly understood. Here, we demonstrate that the transcriptional repressor REV-ERBα is exclusively expressed in TH17 cells, competes with RORγt for their shared DNA consensus sequence, and negatively regulates TH17 cell development via repression of genes traditionally characterized as RORγt dependent, including Il17a. Deletion of REV-ERBα enhanced TH17-mediated pro-inflammatory cytokine expression, exacerbating experimental autoimmune encephalomyelitis (EAE) and colitis. Treatment with REV-ERB-specific synthetic ligands, which have similar phenotypic properties as RORγ modulators, suppressed TH17 cell development, was effective in colitis intervention studies, and significantly decreased the onset, severity, and relapse rate in several models of EAE without affecting thymic cellularity. Our results establish that REV-ERBα negatively regulates pro-inflammatory TH17 responses in vivo and identifies the REV-ERBs as potential targets for the treatment of TH17-mediated autoimmune diseases. : Roles for the circadian protein REV-ERBα have not been extensively explored in the immune system. Amir et al. demonstrate that REV-ERBα acts as a negative regulator of pro-inflammatory TH17 cell development and function, and REV-ERBα ligands are efficacious in mouse models of autoimmunity. Keywords: Th17, RORγt, IL-17A, REV-ERB, SR9009, T cells, autoimmunity, circadian